Conservation agricultural practices for improving productivity and soil health under Rice-linseed cropping system in Vertisol: Conservation agricultural practices for improving productivity and soil health under Rice-linseed cropping system in Vertisol - S K DWIVEDI; R K SATYARAJ GURU (Journal of Oilseeds Research, 2023)
Conservation Agriculture is a farming system that can prevent losses of arable land while regenerating degraded lands (Vlek and Tamene, 2009). Dumanski et al. (2006) explained that conservation agriculture is the integration of ecological management with modern, scientific, agricultural production. It promotes maintenance of a permanent soil cover, minimum soil disturbance, and diversification of plant species. Lal (2001) explained the historical development of agriculture with tillage being a major component of management practices. No-tillage and direct seeding is an effective crop production method for reducing production costs and soil conservation (Huang et al., 2011). Rice – based cropping systems form an integral part of agriculture in Chhattisgarh. Several intensive rice based cropping systems have been identified and are being practiced by the farmers. However, suitable rice based cropping has to be evaluated, to assess the stability in production. Inclusion of oilseeds in the cropping system is more beneficial than cereals followed by cereals (Kumpawat, 2001).